The language barrier : the overlooked challenge to equitable health care - Hussey, Nadia (South African Health Review, 2012)
This chapter examines the effects of language barriers on the access of patients and communities to quality health care. It also looks at communication challenges experienced by health professionals that provide this care. Using a case study of a rural hospital, the chapter highlights some of the challenges posed by the language barrier and explores current methods that English-speaking health professionals at this hospital use to overcome these difficulties. The case study findings indicate that the language barrier decreases work efficiency and the provision of holistic treatment. It makes communication time consuming, which increases frustration levels and decreases empathy, approachability and confidentiality. Current methods for overcoming problems include the use of untrained and ineffective interpreters - usually overworked nurses; linguistic codeswitching; and the use of a selection of key isiXhosa vocabulary. These methods have many drawbacks and are not suitable or sustainable. Recommendations for improving communication include the promotion of a culture of multilingualism, which includes language education as a part of professional development and the employment of trained interpreters. For multilingualism to occur, more research needs to be conducted, and the political will to address this problem must be demonstrated. Overcoming the language barrier needs to be prioritised and commitment must be made to implementing strategies that provide a multilingual patient base with a multilingual healthcare service.

Therapists’ views on working with bilingual Spanish-English clients: A qualitative inverstigation - Santiago-Rivera, Azara. L.; Altarriba, Jeanette; Poll, Norma; Gonzalez-Miller, Normaris; Cragun, Cragun (Professional Psychology: Research and Practice, 2009)
Through semistructured interviews, language switching in therapy was examined with 9 bilingual Spanish and English therapists. Therapists were asked about how and when they switched from one language to another during treatment, as well as the ways in which their clients’ switched languages. After the use of consensual qualitative research methods (C. E. Hill et al., 2005; C. E. Hill, B. J. Thompson, & E. N. Williams, 1997), the results revealed that therapists used language switching as a mechanism to establish trust, bond with clients, and promote disclosure through the use of specific phrases or specific words; particularly, the use of Spanish idiomatic expressions (dichos) served to engage, redirect, and increase client self-understanding and awareness. Therapists reported that their clients switched from English to Spanish when recounting experiences that involved certain emotions (e.g., anger) and represented themselves differently depending on the language they were speaking. Therapists also reported that their clients switched from English to Spanish to improve communication and to connect with them. Future directions for research and implications for training and practice are outlined. (PsycInfo Database Record (c) 2025 APA, all rights reserved)